Qatar : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2008)
This paper is focused on a detailed assessment report on Anti-Money Laundering (AML) and Combating the Financing of Terrorism for Qatar. There is no fundamental principle in Qatari law that would prohibit the courts from applying the money laundering offense to the person who has committed the predicate crime. Qatar has adopted a comprehensive confiscation, freezing, and seizing framework under the AML Law, which enables the authorities to remove all assets linked with a money laundering offense or its predicate.